(3GdYhGUe hGdbhGUe aj GdPH Yf SfI CHj GdbGSes - (3eMeO Hf EHQGgje Hf Ydj Hf GdeQJVj Hf GdeaVd GdMSfj GdbGSej, CHh YHO Gddg, YR GdOjf, ef Bd GdhRjQ,J (B840 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdMi Gdbjhe hef GdOdjd Ydi Pdc ai bhdg YR hLd ai cJGH GdeHjf ai Mb ef jYde Efg ef GdcGPHjf bd gGJhG HQgGfce Ef cfJe UGObjf s
(3BNQgG (B:s
(3EbdhG Ydjge dG CHG dCHjce ef Gddhe Ch TOhG GdecGf GdPi TOhG s
(3GdfSNI HgG MhGTs
(3Ydjg JedcGJs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B300 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B210s
Keywords: (3GdMOjK h GdeUWdMs